Elements of Logic in the Polish School of Mathematics. The contribution of Stanisław Leśniewski - Obojska, Lidia (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2013)
In the presented paper we would like to focus on the scientific activity of the one of the members of the Warsaw School of Logic. It is supposed that the world famous formalisms of Polish logicians were mainly stimulated by Stanisław Leśniewski. If this is true, Leśniewski can be considered as the main ideologist of Warsaw School.The first part of this paper is dedicated to a very brief presentation of the history of Polish logic in the period 1910-1939. Next, we present the main ideas of the Warsaw School of Logic and in particular the contribution of Stanisław Leśniewski: his original system of three theories: protothetics, ontology and mereology and their novelty in comparison with classical thought. Finally, we try to show the influence of Leśniewski’s innovative ideas on other members of the school.